1984
DOI: 10.1128/iai.43.2.670-677.1984
|View full text |Cite
|
Sign up to set email alerts
|

Teichoic acids of Streptococcus agalactiae: chemistry, cytotoxicity, and effect on bacterial adherence to human cells in tissue culture

Abstract: The ratio of teichoic acid to lipoteichoic acid (LTA) in a strain of Streptococcus agalactiae type III was found to be 8:1, with the total amount of LTA being 0.1% of the dry weight of the organism. Purified teichoic acid contained D-alanine and possibly a small amount of D-glucose and was approximately 22 glycerol phosphate units in length. The linkage between each of these units was 1-3. In addition, LTA contained a complex lipid, more glucose, and an unusually high content of a short-chain fatty acid, tride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
4
32
1
Order By: Relevance
“…We found that GBS adhered to the chorion cell surface, invaded, and survived within these cells long enough to transcytose through intact chorion cell monolayers. GBS adhered to primary amnion cells, consistent with previous reports (15), but failed to invade, suggesting that these cells may provide a barrier to penetration of the amniotic membrane.…”
supporting
confidence: 90%
“…We found that GBS adhered to the chorion cell surface, invaded, and survived within these cells long enough to transcytose through intact chorion cell monolayers. GBS adhered to primary amnion cells, consistent with previous reports (15), but failed to invade, suggesting that these cells may provide a barrier to penetration of the amniotic membrane.…”
supporting
confidence: 90%
“…Moreover, there was a correlation between binding to HUVEC with that to the plastic surface, such that strains with high affinity for HUVEC also bound significantly to plastic. This finding suggests that nonspecific forces together with specific binding mechanisms such as lipoteichoic acid-binding and lectin-like interactions participate in binding of GBS to endothelial cells (1,9,17). In other systems charge and hydrophobicity have been shown to significantly affect bacterial binding (15).…”
Section: Discussionmentioning
confidence: 99%
“…This fragment is unique for the bovine species, corresponds to DNA between nucleotides 10 592 and 11 466 of the bovine Kcasein gene (ALEXANDER et al, 1988), and has been used through restriction length polymorphism analysis to ascertain the genotype of cattle at the rc-casein locus (PINDER et al, 1991). Primary cultures of bovine mammary epithelial cells and a transformed bovine mammary epithelial cell line have been used as an in v h model to study cytotoxicity as well as adherence of bacterial pathogens to epithelial cells, Primary cultures of mammary epithelial cells, although placed in an unnatural environment, are considered to resemble more closely actual cells in viva (OLMSTED and NORCROSS, 1992;CIFRIAN et d., 1995); while transformed mammary epithelial cells offer the advantage of homogeneity of target cells used in each experiment, although the process of transformation might affect the expression of surface receptors (GOLDSCHMIDT and PANOS, 1984;OLMSTED and NORCROSS, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This cannot be attributed to the higher number of cells per well in MAC-T monolayers since similar bacterial:epithelial cell ratios were taken into consideration for comparisons. Differences in bin-affinity of groups A and B streptococci between freshly obtained and transformed cell lines have been observed and have been considered to reflect a distinct availability of receptors in either cell type (GOLDSCHMIDT and PANOS, 1984;COURTNEY et al, 1992).…”
Section: Discussionmentioning
confidence: 99%